2009
DOI: 10.1016/j.reseneeco.2008.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Richer and cleaner—At others’ expense?

Abstract: Abstract:Pollution intensive production can be avoided domestically by increased imports and less exports of dirty products. Such trade effects may imply more emissions abroad, or pollution leakages. We study whether such leakages may contribute to the observed inverted relationship between emissions and economic growth -the Environmental Kuznets Curve (EKC). In our case, the rich, open Norwegian economy, we find little evidence for the hypothesis that pollution leakages contribute to explain the EKC. Despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 31 publications
(19 reference statements)
0
6
0
Order By: Relevance
“…Kuznets (1955) suggested that the hypothesis on the theoretical nexus of economic growth and environmental degradation followed an inverted U -shape pattern, the EKC hypothesis. This inverted U -shape curve is also because industrial activity, in the long run, will be shifted to developing nations to reduce pollution (Cherniwchan, 2012; Fæhn and Bruvoll, 2009). Besides, McConnell (1997) came out with empirical results that validate the EKC hypothesis.…”
Section: Sustainable Development – Energy Pollutant Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuznets (1955) suggested that the hypothesis on the theoretical nexus of economic growth and environmental degradation followed an inverted U -shape pattern, the EKC hypothesis. This inverted U -shape curve is also because industrial activity, in the long run, will be shifted to developing nations to reduce pollution (Cherniwchan, 2012; Fæhn and Bruvoll, 2009). Besides, McConnell (1997) came out with empirical results that validate the EKC hypothesis.…”
Section: Sustainable Development – Energy Pollutant Emissionsmentioning
confidence: 99%
“…Several studies have put forward the studies on the trade-off between economic growth and environmental degradation: such as the European Union (Bekun et al ., 2019), Qatar (Salahuddin and Gow, 2019), Turkey (Ozcan et al , 2018), 34 Asian countries (Le et al , 2019), 63 countries (Ahmed et al , 2019), Brazil (Zambrano-Monserrate et al , 2016), just to name a few. Different approaches used by scientists have attempted to scrutinize this trade-off from the context of different energy forms, non-energy-related factors, socioeconomic and other factors.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we believe that developed countries, producers and consumers and are to be blamed for the aftermaths of the environmental leakages. Developing countries imports dirty products and this lead to displacement of emissions abroad and often an overall increase in the global pollution [16]. Hence, the present study was designed to determine the cost of health problems associated with air pollution, while incorporating environmental leakage.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper, we consider environmental leakage, which happens when rich country imports dirty products from developing countries. This phenomenon leads to displacement of emissions abroad and often an increase in the global pollution [16]. According to [17], the consumption-based approach is necessary to calculate the impact of production activities.…”
Section: Introductionmentioning
confidence: 99%
“…Using input-output decomposition, Levinson (2009) calculates that the transfer of polluting industries overseas accounted for around 10% of US emissions reductions over the period 1987-2001. Using both historical data and CGE modelling, Faehn and Bruvoll (2009) find that economic growth was not associated with leakage impacts in the form of net imports of 'dirty' goods.…”
Section: Economic Growth and Pollution Leakagementioning
confidence: 97%